Return migration and occupational choice - Matloob Piracha; Florin P. Vadean (Institute for the Study of Labor (IZA), 2009)
This paper explores the impact of return migration on the Albanian economy by analysing the occupational choice of return migrants while explicitly differentiating between self-employment as either own account work or entrepreneurship. After taking into account the possible sample selection into return migration, we find that the own account workers have characteristics closer to non-participants in the labour market (i.e. lower education levels), while entrepreneurship is positively related to schooling, foreign language proficiency and savings accumulated abroad. Furthermore, compared to having not migrated, return migrants are significantly more likely not to participate in the labour market or to be entrepreneurs. However, after a one year re-integration period, the effect on non participation vanishes and that on entrepreneurship becomes stronger. As for non-migrants, the migration experience would have increased their probability to be entrepreneurs showing the positive impact of migration on job creating activities in Albania.
urn:nbn:de:101:1-20090119182
Keywords: C35; F22; J24; 330; Occupational choice; return migration; sample selection; Rückwanderung; Berufswahl; Selbstständige; Unternehmer; Albanien